A novel hybrid half‐bridge LLC resonant converter with double resonant tanks for high step‐down applications. (20th September 2022) - Lu, Song; Ma, Hongbo; Yi, Junhong; Li, Xiaobin; Li, Jian
Abstract: Conventional half‐bridge (HB) LLC converters have been a good candidate for the first stage in the two‐stage conversion structure because of its high conversion efficiency and high frequency operation ability. However, the voltage gain is only 0.5 exclusive of the transformer, resulting in the reduced efficiency for high step‐down applications. In order to solve this issue, in this paper, a novel hybrid HB LLC converter with double resonant tanks is firstly presented for high step‐down ratio applications. The distinctive features of the proposed converter are as follows: (1) the voltage gain of 0.25 is achieved by incorporating the switched capacitor circuit. Thus, the primary turns number for the transformer is halved compared with conventional HB LLC converters. Correspondingly, the smaller primary side winding losses and transformer volume can be implemented. (2) The power splitting and low input current ripple can be obtained due to the employed double resonant tanks. Thus, the uniform thermal distribution and low input filter capacitance are the second advantage for the proposed converter. (3) Soft switching over the entire operation range still can be maintained with larger magnetics inductance. The detailed operation principles, circuit analysis, and resonant tank design for the proposed converter are introduced and presented. A hardware prototype with 36–60 V input, 3 V/50 A‐output is built to demonstrate the declared features of the proposed hybrid converter. Abstract : The proposed hybrid HB LLC converter with double resonant tanks, photograph of the developed prototype and measured output voltage and efficiency under different input and output current.